Preliminary e ects of mathematics curriculum development for primary school student teachers in Sárospatak Comenius Campus - Gyöngyösi-Wiersum, Erika (Teaching Mathematics and Computer Science, 2017)
Hungarian students’ mathematics performance has been getting weaker in the past few years. A possible solution to stop this tendency is to develop curriculum. Therefore, Hungarian researchers have been refining a particular framework of curriculum development in primary school teacher training programmes. The national curriculum is designed on the assumption that learning can be broken into a sequence of levels and students can evenly succeed in gaining knowledge at successive levels. In this paper, we want to discuss how to reduce students’ difficulties with different background to grow competence at successive levels.